A STUDY OF THE STUDENTS’ LEARNING STYLE AT THE SECOND GRADE OF SMP PESANTREN GUPPI SAMATA - Radhiyatul Jamilah; Ria Hajriah (Universitas Sembilanbelas November Kolaka, 2020)
The research aimed to analyze students’ receptive learning style, processing learning style, and expressive learning style in the second-grade students of SMP PesantrenGuppiSamata. The research was in qualitative method, it collects, analyzes, and interprets the phenomenon of learning style in the second-grade students’ of VII B class in SMP GuppiSamata as the subject of research. The data was collected using observation and interviews. The result of this research showed that each student is different based on how they receive, process, and express their information. There were 17 students in VII B class. For the receptive learning style, there were three visual learners, five auditory learners, six kinesthetic learners, and the other three students who used multiple learning styles. In processing learning style there were seven left-brain learners and ten mid-brain learners. In expressive learning style, there were two students used creatively as output area, nine students used writing as output area, one student used thinking as output area, two students used creative and thinking as output area, and two students can use multiple output area. The research helped the students to know and realize their own learning style, providing a contribution to the teacher to plan learning strategy and learning activity that will suit each learning style and to be a new reference andupdates the existing study.